Understanding the Relationship between Nursing Home Experience with HIV and Patient Outcomes - Meyers, David J. (Med Care, 2021)
BACKGROUND: As the population with HIV continues to age, the need for nursing home (NH) care is increasing. OBJECTIVES: To assess whether NH’s experience in treating HIV is related to outcomes. RESEARCH DESIGN: We used claims and assessment data to identify individuals with and without HIV who were admitted to NHs in 9 high HIV prevalent states. We classified NHs into HIV experience categories and estimate the effects of NH HIV experience on patient’s outcomes. We applied an instrumental variable using distances between each individual’s residence and NHs with different HIV experience. SUBJECTS: 5,929,376 admissions for those without HIV and 53,476 admissions for residents with HIV. MEASURES: Our primary outcomes were 30-day hospital readmissions, likelihood of becoming a long stay resident, and 180-day mortality post hospital discharge. RESULTS: Residents with HIV tended to have poorer outcomes than residents without HIV, regardless of the NH they were admitted to. Residents with HIV admitted to high HIV experience nursing homes were more likely to be readmitted to the hospital than those admitted to nursing homes with lower HIV experience (19.6% in 0% HIV NHs, 18.7% in 05% HIV NHs and 22.9% in 5–50% HIV NHs). CONCLUSIONS: Residents with HIV experience worse outcomes in NHs than residents without HIV. Increased HIV experience was not related to improved outcomes.